2022
DOI: 10.52296/vje.2022.132
|View full text |Cite
|
Sign up to set email alerts
|

The Predictors of Students’ Satisfaction and Academic Achievements in Online Learning Environment in Higher Education

Abstract: Student satisfaction is crucial in remote education course evaluation because it is linked to the quality of online programs and student academic performance. Meanwhile, self-regulated learning is crucial in both traditional and online learning environments since it involves the ability to organize, manage, and control their learning process. In this study, the authors tested the correlations between student satisfaction and academic achievement involving student characteristics, self-regulated learning, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…However, perceived usefulness has no impact on student satisfaction. Consistent with the previous finding, Dinh et al (2022) found that self-efficacy and self-regulated learning predict student satisfaction, thus leading to favorable academic outcomes and achievements. Based on the survey conducted on 1,195 university students from Thailand, Malaysia, Indonesia, and China, Yan-Li et al (2022) documented a surprising result where more than 60% of the students were not satisfied with their online learning courses due to low online learning readiness in terms of online learning preference, direction, self-efficacy, and hardware-soft skill supports.…”
Section: Student Satisfactionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, perceived usefulness has no impact on student satisfaction. Consistent with the previous finding, Dinh et al (2022) found that self-efficacy and self-regulated learning predict student satisfaction, thus leading to favorable academic outcomes and achievements. Based on the survey conducted on 1,195 university students from Thailand, Malaysia, Indonesia, and China, Yan-Li et al (2022) documented a surprising result where more than 60% of the students were not satisfied with their online learning courses due to low online learning readiness in terms of online learning preference, direction, self-efficacy, and hardware-soft skill supports.…”
Section: Student Satisfactionsupporting
confidence: 89%
“…This finding suggests that when there is an increase in self-efficacy, learner-content interaction, and learnerlearner interaction, the level of student satisfaction in the online environment will be expected to increase. In terms of self-efficacy, the finding of the current study is in line with a study conducted by (Karim et al, 2021;Dinh et al, 2022;Aldhahi et al, 2022). Strong selfefficacy gives students the confidence to believe they can complete any task, no matter how challenging.…”
Section: Descriptive Analysis and Reliabilitysupporting
confidence: 88%
See 3 more Smart Citations